Subtitle Strategic Of The Sims FreePlay Translated Into Bahasa Indonesia - Suwondo, Janisa Putri; Noryatin, Yeni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify and analyze the translation strategies used in the subtitles of The Sims FreePlay video game from English into Indonesian. The main focus of this research is on the subtitle translation strategies proposed by Gottlieb (1992), namely transfer, paraphrase, imitation, and condensation. Video games as a form of digital media require effective subtitle translation so that players can understand the storyline, instructions, and dialogues presented in the game. Therefore, analyzing the strategies used in subtitle translation is important to determine how the original message is conveyed in the target language. This research employed a descriptive qualitative method. The data were collected through documentation by recording and compiling the subtitle texts that appear in the game. The collected data were then analyzed to identify the types of translation strategies applied and to determine which strategy was used most frequently. The findings revealed that the transfer strategy was the most dominant, accounting for 44.44% of the total data, followed by paraphrase (22.22%), imitation (22.22%), and condensation (11.11%). In addition, this study also evaluated the translation quality based on three aspects: accuracy, acceptability, and readability. The analysis showed that the average score for each aspect was 3, indicating that the translations were generally accurate, acceptable, and easy for Indonesian players to understand. Overall, this study contributes to translation studies, especially in the context of digital media such as video games, and can serve as a reference for translators, students, and researchers.